Determining the Frequency of Metabolic Syndrome in Gout Patients in Rheumatology Clinics of Sari in 2023-24 - Hengameh Babaee; Maryam Mobini; Fatemeh Niksolat; Aref Hoseinian Amiri; Reza Ali Mohammadpour (Iranian Journal of Diabetes and Obesity, 2025)
Objective: Gout and metabolic syndrome (MetS) are associated with increased risk of cardiovascular involvement. The aim of the current study was to evaluate the frequency of MetS and its components in patients with gout. Materials and Methods: This cross-sectional study was conducted on 150 patients with gout in Sari, Iran. The demographic, clinical and laboratory variables of the patients were recorded. The MetS was defined by the 2005 National Cholesterol Education Program (NCEP/ATP III) and International Diabetes Federation (IDF). Then, patients with gout with and without metabolic syndrome were compared in terms of demographic and clinical characteristics. Data analysis was performed by SPSS (version 19), at a significance level of < 0.05. Results: The mean age of the patients was 50.17±15 year. Based on the NCEP/ATP III and IDF criteria, 88 (58.7%) and 90 (60%) were diagnosed with MetS, respectively. Age, body mass index, and duration of gout were significantly higher in patients with MetS criteria (P< 0.05). Conclusion: The frequency of MetS was found about 60% of patients with gout. Hypertriglyceridemia and central obesity are two more prevalent components of MetS in our patients. The association of MetS and cardiovascular diseases highlights the importance of attention and management of this condition in patients with gout.